Sterigmatomyces halophilus β-glucan improves the immune response and bacterial resistance in Pacific red snapper (Lutjanus peru) peripheral blood leucocytes: In vitro study. Issue 78 (July 2018) - Reyes-Becerril, Martha; Guardiola, Francisco A.; Sanchez, Veronica; Maldonado, Minerva; Angulo, Carlos
Abstract: β-Glucans are naturally occurring polysaccharides that are produced by bacteria, fungi and yeast. They are considered immunostimulants in fish acting on non-specific defense mechanism. Yeast-derived glucans from cell wall ( Sterigmatomyces halophilus, β-Gluc/Sh) have been used for this purpose in this study. Therefore, an in vitro assay using peripheral blood leucocytes (PBLs) from Pacific red snapper was performed to evaluate the stimulant effects of β-Gluc/Sh and zymosan A (positive control) for 12 and 24 h and after bacterial challenge with Aeromonas hydrophila at 24 h. In addition, structural characterization of this marine yeast glucan was performed by proton nuclear magnetic resonance (NMR) revealing structures containing (1-6)-branched (1-3)-β-D-glucan. PBLs responded positively to β-Gluc/Sh where cell viability was higher than 80%. After challenge, β-Gluc/Sh was able to inhibit cytotoxicity caused by A. hydrophila, highlighting that the PBLs incubated with β-Gluc/Sh significantly increased the non-specific immune response, such as phagocytic activity, respiratory burst, nitric oxide and peroxidase activities followed by an increase in superoxide dismutase and catalase activities after 12 and 24 h post-stimulation and after challenge with the pathogen. Regarding induction of antioxidant gene expression, it was more pronounced in stimulated β-Gluc/Sh leucocytes compared to other groups at all experimental times of the trial and after bacterial challenge. Indeed, our results clearly showed the ability of leucocytes to strongly react to β-Gluc/Sh with an increase in cytokine gene expression, particularly the IL-1β, IL-10 and IL-17 genes. These results confirm that S. halophilus yeast-derived β-glucan, isolated from an extreme marine environment, is beneficial for increasing innate immune response and enhancing resistance against A. hydrophila in vitro . Highlights: Sterigmatomyces halophilus β-glucan enhances immune parameters in fish leukocytes. Structural characterization by (NMR) revealing (1-6)-branched (1-3)-β-D-glucan. β-Gluc/Sh was able to inhibit cytotoxicity caused by A. hydrophila in PBLs. Antioxidant SOD and CAT activity was increased in β-Gluc/Sh-stimulated PBLs. Cytokine gene expression confirms the immunoestimulatory effects of β-Gluc/Sh.